Effect of inlet air velocities on freshwater mass and heat transfer rates in an air-water harvester 0.5 PK - M. Mirmanto; Y.A. Padang; A.K. Mari (Dinamika Teknik Mesin, 2025)
During the dry season, some regions experience a shortage of clean water due to drought. Air water harvesters utilize the principle of condensation to produce clean freshwater from humid air can be alternative to solve the drought. This device works by condensing water vapour in the air using an evaporator. The focus of this study was on the effect of air velocities on the freshwater production and heat transfer rates. This research was conducted experimentally using refrigerant R134a as the working fluid. The compressor used was a 0.5 HP rotary compressor. The inlet air velocities applied were 0 m/s, 1.5 m/s, and 3 m/s. The results showed that the highest average mass of water obtained was 3.73 kg using the air velocity variation of 3 m/s. Meanwhile, the total heat flow absorbed by the evaporator from the air was highest also at the air velocity variation of 3 m/s, which was 1238.22 W. Increasing inlet air velocities raises the freshwater production and heat transfer rates.